Pengaruh Sikap Dan Norma Subjektif Konsumen Terhadap Perilaku Berbelanja Pada Supermarket Palu Mitra Utama Di Kota Palu - Asngadi (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2014)
This study is aimed (1) to observe the establishment of consumer’s attitude and consumer’s subjective norm to spend their money toward the Palu Mitra Utama Supermarket based on the reasoned action theory, (2) to identify the effect of attitude and subjective norm on the customer’s intention to spend their money at Palu Mitra Utama Supermarket, (3) to identify the effect of attitude and subjective norm of both customers who have a high and low spending intention on their spending behavior at the Palu Mitra Utama Supermarket. This study is conducted in two analysis stages using the conclusive research model based on the reasoned action theory. The first stage is analysing the effect of attitude and subjective norm on the spending intention. The second stage is classifying attitude and subjective norm based on the rate of strength or weakness of the spending intention and their effect on the spending behavior. The variables measurement are includes: (1) attitude variable, which is conducted by comparing the components of customer’s belief with evaluation on the supermarket, (2) subjective norm variable, which is conducted by comparing the component of customer’s normative belief with the component of consumer’s motivation to comply the reference’s opinion. The result of this study indicate that: (1) consumer’s belief and evaluation on the supermarket shape their positive attitude toward such supermarket; whereas customer’s normative belief and their motivation to follow the reference’s opinion shape their positive subjective norm toward such supermarket, (2) undoubtedly, consumer’s attitude and subjective norm has a statistically significant effect on the customer’s spending intention, while the customer’s belief and evaluation shape such customer’s positive attitude, (3) the attitude and subjective norm of those customer who has a statistically weak spending intention has no significant effect on the customer’s spending behavior, whereas the attitude and subjective norm of those customer who has a statistically strong spending intention has a statistically significant effect on the customer’s spending behavior.